2000
DOI: 10.1021/es991410u
|View full text |Cite
|
Sign up to set email alerts
|

Biologically Enhanced Dissolution of Tetrachloroethene DNAPL

Abstract: One major problem with tetrachloroethene (PCE) contamination of aquifers is its ability to form dense, nonaqueous-phase liquids (DNAPL), which can act as a persistent contamination source for decades. Batch studies were performed to determine the potential for biological reductive PCE dehalogenation at high concentration and the effect on competing microorganisms, including methanogens and homoacetogens. Results show that PCE dehalogenation can be obtained at saturation concentration (>0.9 mM). Also, trichloro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
175
3
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(199 citation statements)
references
References 29 publications
(44 reference statements)
20
175
3
1
Order By: Relevance
“…Bioenhancement of NAPL dissolution has been observed experimentally in sand column and box experiments (19,21,25). Further experiments with batch cultures have demonstrated the ability of some dechlorinating cultures to transform a mixed (PCE/tridecane) NAPL (17,26) and to achieve complete PCE-DNAPL dissolution (20). Efforts to model metabolic reductive dechlorination have included substrate fermentation, nonlinear dechlorination kinetics (with and without competitor, product, and selfinhibition), and growth of competitor populations (e.g., refs 22, 27-30).…”
Section: Form Approved Omb No 0704-0188mentioning
confidence: 83%
See 2 more Smart Citations
“…Bioenhancement of NAPL dissolution has been observed experimentally in sand column and box experiments (19,21,25). Further experiments with batch cultures have demonstrated the ability of some dechlorinating cultures to transform a mixed (PCE/tridecane) NAPL (17,26) and to achieve complete PCE-DNAPL dissolution (20). Efforts to model metabolic reductive dechlorination have included substrate fermentation, nonlinear dechlorination kinetics (with and without competitor, product, and selfinhibition), and growth of competitor populations (e.g., refs 22, 27-30).…”
Section: Form Approved Omb No 0704-0188mentioning
confidence: 83%
“…Several studies with pure cultures (see Table S1, Supporting Information) and with mixed dechlorinating consortia (e.g., [17][18][19][20][21][22][23][24] have shown that bacterial PCE dechlorination occurs at or near saturated PCE concentrations. For instance, Desulfuromonas michiganensis strain BB1 was reported to dechlorinate at saturated PCE concentrations and to grow in the presence of PCE DNAPL (4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among potential in situ remediation technologies, microbial reductive dechlorination has emerged as an attractive DNAPL source zone remedy (Da Silva et al, 2006;Sleep et al, 2006;Schaefer et al, 2010), and as a source zone polishing step to control residual contaminant concentrations following aggressive physicochemical treatment (Mravik et al, 2003;Ramsburg et al, 2004;Christ et al, 2005). During source zone bioremediation, microbial activity lowers dissolved-phase contaminant concentrations, thereby increasing the driving force for contaminant dissolution from the DNAPL to the aqueous phase, a process commonly referred to as bioenhanced dissolution (Yang and McCarty, 2000;Cope and Hughes, 2001;Yang and McCarty, 2002;Adamson et al, 2003;Sleep et al, 2006;Glover et al, 2007;4 Amos et al, 2008). While dissolution enhancements may lead to short term increases in dissolved phase cis-DCE concentrations, the overall source longevity and associated cleanup times decrease, potentially resulting in reduced long-term risk.…”
Section: Introductionmentioning
confidence: 99%
“…Carr et al, 2000;Yang and McCarty, 2000;Cope and Hughes, 2001;Sleep et al, 2006;Amos et al, 2008Amos et al, , 2009Schaefer et al, 2010;Philips et al, 2011). This variability in dissolution enhancement has been attributed to several factors, including differing microbial populations, electron donor limitations, competitive and threshold inhibitions, and competitor populations (e.g., methanogens), as well as changing flow conditions due to gas formation, microbial growth, and experimental design.…”
Section: Introductionmentioning
confidence: 99%